Survival and inactivation of Salmonella enterica serovar Typhimurium on food contact surfaces during log, stationary and long-term stationary phases. (December 2019) - Djebbi-Simmons, Dorra; Xu, Wenqing; Janes, Marlene; King, Joan
Abstract: One of the most important transmission routes of foodborne pathogens is through contaminated food contact surfaces. In this study, we investigated the survival and inactivation of Salmonella enterica serovar Typhimurium on frequently used food contact surfaces in household settings, including plastic cutting board (CB), formica laminate (LA), and stainless steel (SS) surfaces. S. Typhimurium at log (6 h), stationary (24 h), or long-term stationary (LTS) (14 days) phases were evaluated. Results showed that, at medium and high microbial loads, LTS phase cells had significantly higher survivor population compared to log and stationary phase cells at 24 h after inoculation ( p  < 0.05). Disinfection study showed that LTS phase cells were very resilient to sodium hypochlorite when the initial microbial load was high with disinfection efficacy ranging from 26 to 35%. Scanning electron microscopy of these surfaces at 24 h after inoculation with a high microbial load revealed an early biofilm structure. Highlights: Long-term stationary (LTS) Salmonella on food contact surfaces were studied. At high microbial load, LTS cells showed highest survival population. LTS phase cells were most resilient to sodium hypochlorite treatment. Early biofilm formation may contribute to the resilience.